2001
DOI: 10.1103/physrevb.64.155301
|View full text |Cite
|
Sign up to set email alerts
|

Striped states in quantum Hall effect: Deriving a low-energy theory from Hartree-Fock

Abstract: There is growing experimental and theoretical evidence that very clean two dimensional electron systems form unidirectional charge density waves (UCDW) or "striped" states at low temperatures and at Landau level filling fractions of the form ν = M + x with 4 < M < 10 an integer and 0.4 < ∼ x < ∼ 0.6. Following previous work, we model the striped state using a Hartree Fock approach. We construct the low energy excitations of the system by making smooth deformations of the stripe edges analogous to the construct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 18 publications
4
51
1
Order By: Relevance
“…Most microscopic theories for the anisotropic state at ν = 9/2 (and in higher Landau levels) were built on this proposal. [27][28][29][30][31][32][33] The resulting picture of the stripe state is an array of "sliding" Luttinger liquids.…”
Section: 18mentioning
confidence: 99%
“…Most microscopic theories for the anisotropic state at ν = 9/2 (and in higher Landau levels) were built on this proposal. [27][28][29][30][31][32][33] The resulting picture of the stripe state is an array of "sliding" Luttinger liquids.…”
Section: 18mentioning
confidence: 99%
“…[34,35,36,37,38,39,40]). Recent work on these interesting phases of the two-dimensional electron gas has revealed that magnetic symmetry plays a crucial role in low-energy dynamics of these states.…”
Section: Discussionmentioning
confidence: 99%
“…2,3͒ and the first experimental observation in high Landau levels via the magnetoresistance anisotropy measurement in 1999. 4,5 Many related phenomena, e.g., transport via internal edge state excitations, [6][7][8] liquid crystal phases, 1,9 reorientation of stripe directions, [10][11][12] and reentrant integer quantum Hall effect, 13 have been widely explored both theoretically and experimentally in this context. Stripe formation at fractional filling factors ϭ(2Nϩ1)/(4Nϩ4) corresponding to the composite fermion filling factor *ϭN ϩ1/2 was also proposed to have energy lower than the conventional Laughlin liquid, composite-fermion Fermi sea, or paired composite-fermion state.…”
Section: Introductionmentioning
confidence: 99%